ADAPTING TO THE HYBRID WORKFORCE: HR STRATEGIES FOR MANAGING REMOTE AND ON-SITE EMPLOYEES IN 2024 - Vera Herlina Mustari; Klemens Mere; Alisyah Pitri; Trio Ongko Wibowo; Nilfatri Nilfatri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The rise of hybrid work models has transformed traditional workplace dynamics, blending remote and on-site work environments. As organizations navigate this new landscape, Human Resources (HR) departments face the challenge of developing effective strategies to manage and support both remote and on-site employees. This literature review explores the evolving strategies that HR professionals must adopt to address the unique needs and challenges associated with hybrid workforces. The review synthesizes recent research and best practices on managing remote teams, fostering inclusivity, maintaining productivity, and ensuring employee engagement in a hybrid setting. Key areas of focus include the integration of digital tools to support communication and collaboration, the development of flexible work policies, and the creation of robust performance management systems that accommodate diverse work environments. By examining contemporary HR approaches and technological advancements, this study aims to provide insights into effective management strategies that can enhance organizational performance and employee satisfaction in the hybrid work era.